Odpowiedź :
ZADANIE 1
a) [tex]x^{2} + 2xy - y^{2} + 2x^{2} - 2xy + y^{2} = 3x^{2}[/tex]
b) [tex]2a - b + 3a - 7b = 5a - 8b[/tex]
c) [tex]ab + c - ab - 2c = -c[/tex]
d) [tex]x^{2} + 2x - 7 - x^{2} - 3x + 3 = -x - 4[/tex]
ZADANIE 2
a) [tex](x+y)+(x-5)+(-5-4y)=x+y+x-5-5-4y=2x-3y-10[/tex]
b) [tex]7x-(2x-y)-(-3y-7)=7x-2x+y+3y+7=5x+4y+7[/tex]
c) [tex](3x-y-1)-(4x-2y-2)=3x-y-1-4x+2y+2=-x+y+1[/tex]
d) [tex]-(8x^{2} +4x)+(-16x^{2} -2x)=-8x^{2} -4x-16x^{2} -2x=-24x^{2} -6x[/tex]
e) [tex]6ab+7-(5ab-12)=6ab+7-5ab+12=ab+19[/tex]
ZADANIE 3
a) [tex]4(k+3)=4k+12[/tex] (nie wiem czy tam było k, czy coś innego)
b) [tex]-3(x-y)=-3x+3y[/tex]
c) [tex](12k-4)*(-1)=-12k+4[/tex]
d) [tex](7x-y)*(-5)=-35x+5y[/tex]
e) [tex]x(x-1)=x^{2} -x[/tex]
f) [tex]-a(-2a+1)=2a^{2} -a[/tex]
g) [tex]a(a^{2} -2a-2)=a^{3}-2a^{2}-2a[/tex]
h) [tex]5a(-\frac{1}{2} a+\frac{1}{3} )=-\frac{5}{2}a^{2}+ \frac{5}{3} a=-2\frac{1}{2}a^{2}+1 \frac{2}{3} a[/tex]
PODKREŚLENIE ZREDUKOWANYCH WYRAZÓW W ZAŁĄCZNIKU!!